Low Cost Self-Testing Implementation for MISTY1 Cryptographic Algorithm - Tirtea, R.; Vladutiu, M.; Deconinck, G. (2007 5th IEEE International Conference on Industrial Informatics, 2007)
Side-channel attacks (i.e. fault analysis attacks) exploit vulnerabilities generated by faults in cryptographic implementations. Given the consequences of a successful attack (which can retrieve key information with a quite low cost), error detection mechanisms need to be implemented to protect cryptographic implementations. However the available mechanisms generate large overhead both in hardware and time and other low cost error detection techniques are required. We propose in this paper a new error detection technique, relying on information redundancy. This technique uses complemented duplication. A case study is presented for MISTY1 cryptographic algorithm. The error propagation for MISTY1 is analyzed. Trade-off analysis of different resources required for detection mechanisms is included. The cost of the detection mechanism using this technique is lower than the costs of the previously available techniques.